Active edible coatings and films with Mediterranean herbs to improve food shelf-life. Issue 9 (30th March 2022) - Pérez-Santaescolástica, Cristina; Munekata, Paulo E. S.; Feng, Xi; Liu, Ying; Bastianello Campagnol, Paulo Cezar; Lorenzo, Jose M.
Abstract: The main reasons for food decay are oxidative reactions and bacterial growth. The food industry has tried to solve these problems either by incorporating additives into foods or by implementing different packaging techniques. However, there is a tendency to incorporate additives into packaging materials, especially those of natural origin. Due to the multiple properties and their extensive accessibility, Mediterranean herbs have been used since ancient times for culinary and pharmacological purposes. This review includes up-to-date information concerning the materials employed and the techniques to produce Mediterranean herbal coatings and films, as well as the sensory changes during the storage within different food categories. Mediterranean herbs have polyphenols, terpenoids, and flavonoids with antimicrobial and antioxidant activity that can used to produce different active systems: sachets, multilayers, labels and coatings. Moreover, the use of essential oils or volatile essential oils from Mediterranean herbs in coatings and films can improve the properties of packaging system and extend the shelf-life of muscle products, fruit and vegetables. The impact of essential oils components in the sensory attributes of coated foods is the current main challenge for the use of these bioactive components in active packaging.